Numerical simulation and prediction of the performance of a direct injection turbocharged diesel engine. (November 2013) - Menacer, Brahim; Bouchetara, Mostefa
Increases in fuel prices are constraining car manufacturers to produce highly efficient engines, noting greater regulation in terms of pollutant emissions. The greater complexity of modern engines has rendered the prototyping phase long and expensive. This is where engine modeling has in recent years become extremely useful and an indispensable tool when developing new engine concepts. This study deals with the numerical simulation and performance prediction for a turbocharged diesel engine with direct injection. To predict engine performance we developed a computer program for simulating the operation of a turbocharged diesel engine, and used the commercial software GT-Power to validate the simulation results. We then carried out a comparative study of indicated mean effective pressure, mean effective pressure, power, torque and brake specific fuel consumption obtained by an analytical model for thermodynamic cycle simulation of a turbocharged diesel engine using a computer program developed in Fortran and GT-Power. The Fortran program that was developed is currently used for modeling and the simulation of engine performance.